A Sensitive Method for Detecting Peptide-specific CD4+ T Cell Responses in Peripheral Blood from Patients with Myasthenia Gravis - Sharma, Sapna; Malmeström, Clas; Lindberg, Christopher; Meisel, Sarah; Schön, Karin; Verolin, Martina; Lycke, Nils Yngve (Frontiers in Immunology, 2017)
Myasthenia gravis (MG) is an autoimmune neurological disorder typified by skeletal muscle fatigue and most often production of autoantibodies against the nicotinic acetylcholine receptor (AChR). The present study was undertaken to assess the extent of AChR-peptide recognition in MG patients using co-culturing (DC:TC) of autologous monocyte-derived dendritic cells (DC) and highly enriched CD4+ T cells from the blood as compared to the traditional whole peripheral blood mononuclear cell (PBMC) cultures. We found that the DC:TC cultures were highly superior to the PBMC cultures for detection of reactivity towards HLA-D-restricted AChR-peptides. In fact, whereas DC:TC cultures identified recognition in all MG patients the PBMC cultures failed to detect responsiveness in around 40% of the patients. Furthermore, reactivity to multiple peptides was evident in DC:TC cultures, while PBMC cultures mostly exhibited reactivity to a single peptide. No healthy control (HC) CD4+ T cells responded to the peptides in either culture system. Interestingly, whereas spontaneous production of IFNγ and IL-17 was observed in the DC:TC cultures from MG patients, recall responses to peptides enhanced IL-10 production in 9/13 MG patients, while little increase in IFNγ and IL-17 was seen. Healthy controls did not produce cytokines to peptide stimulations. We conclude that the DC: TC culture system is significantly more sensitive and better identifies the extent of responsiveness in MG patients to AChR-peptides than traditional PBMC cultures.